4.4k views
3 votes
14. f(x) = -x4 + x² + 4; x = -1

Use synthetic division to evaluate the function for the indicated value of x

User Gakio
by
5.0k points

1 Answer

5 votes

Answer:

f(-1) = 4

Explanation:

See below for the synthetic division tableau. The remainder is 4, hence ...

f(-1) = 4

___

IMO, in this function it is far easier just to substitute -1 for x. Since the only terms are of even degree, the value of f(-1) is the sum of the coefficients:

f(-1) = -1 +1 +4

f(-1) = 4

14. f(x) = -x4 + x² + 4; x = -1 Use synthetic division to evaluate the function for-example-1
User Akaltar
by
5.7k points